Efek Kepemilikan Institusional, Insentif Pajak dan Profitabilitas Terhadap Tax Avoidance - Nuramal, Nuramal; Gunawan, Gunawan (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2024)
This study aims to examine the influence of institutional ownership, tax incentives and profitability on tax avoidance. The type of research used in this study is quantitative research with a descriptive approach to research certain populations and samples. The population used in this study is the financial statements of manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange in 2020 – 2023 totaling 80 companies obtained directly through the official website of the Indonesia Stock Exchange, namely www.idx.co.id. The sample selection in this study uses the purposive sampling method, which is to select samples through certain criteria. The research sample is 21 company data with a four-year maturity period so that it was found that the total research sample is 84 financial report data of manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange. The results of the study found that partial institutional ownership did not have a significant effect on tax avoidance, tax incentives partially had a significant effect on tax avoidance and profitability partially did not have a significant effect on tax avoidance.